Evolution of the Danube River’s islands on the Bulgaria-Romania border over the last century - Gabriela Ioana-Toroimac; Marina Vîrghileanu (PLoS ONE, 2025)
The border line between Bulgaria and Romania was established a century ago on the Danube River’s thalweg, going around islands. Over time, islands migrated; to avoid conflicts, islands located on the border line are declared neutral territory by both countries and they exit from use. In this context, the paper aims to draw conclusions on the spatial dynamics of the Danube River’s sandy islands along the Bulgaria-Romania border. This approach is mostly a GIS work on various documents over the last century, with interpretations specific to fluvial geomorphology. Our paper showed patterns of evolution of islands. (i) The trajectory of half of the islands can be reconstituted over the last century (i.e., merging with each other and/or migrated). The trajectory of the other half of the islands can be redrawn over the last half of the century. The form and dimensions of islands did not statistically change at any time scale. (ii) At the scale of the last decades, we noticed the slow formation of bars by lee deposition due to sediment excess and then migration of alluvial bars until merging with an island or with the bank, followed by stabilization due to vegetation recruitment. (iii) Islands and their bars migrated on the countries’ border line, but their evolution is slow in time. Our paper invites national authorities to periodically inventory the geomorphological trajectory of islands and bars, but to transfer the decision-making process for stable islands at local scale in order to put them into green use with benefits for local communities.